LONG TERM CARE AS A HUMAN RIGHT. (11th November 2018) - Cox, C; Doron, I; Benny, S; Giannaraki, E
Abstract: Article 25 of the Declaration of Human Rights proclaims the right of every person to health and medical care in the event of sickness, disability or old age. In its most generic form, long term care refers to all of the supports, informal and formal, offered in the home, community, and institutions to assist persons with functional limitations. The majority of long term care recipients are older adults struggling with disabilities and for whom such services can be pivotal in maintaining their ability to remain at home, deterring further deterioration. The right to long term care has not yet been established and is generally confused with the rights of institutionalized persons. Using the IOPHRI (Spanier and Doron, 2017) an index measuring human rights, this paper compares the legislative right to LTC, community/home based care and institutional, in 9 countries. The results indicate considerable variance among countries in the extent to which the right exists, with most having rights with significant limitations. Most important is that the study offers insight into aging policy and the extent to which it sustains human rights that are critical to the well-being of older adults.